The Visible Hand: The Managerial Revolution in American BusinessChandlerAlfred D.Jr. The Visible Hand: The Managerial Revolution in American Business (Cambridge, Massachusetts: The Belknap Press of Harvard University Press, 1977), 608 pp., $18.50. - George, Claude S. (Academy of Management Review, 1979)
The article reviews the book ?The Visible Hand: The Managerial Revolution in American Business,? by Alfred D. Chandler Jr.